2021
DOI: 10.1101/2021.05.11.443579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Segregation and integration of the functional connectome in neurodevelopmentally ‘at risk’ children

Abstract: Functional connectivity within and between Intrinsic Connectivity Networks (ICNs) transforms over development and supports high order cognitive functions. But how variable is this process, and does it diverge with altered cognitive developmental trajectories? We investigated age-related changes in integration and segregation within and between ICNs in neurodevelopmentally at-risk children, identified by practitioners as experiencing cognitive difficulties in attention, learning, language, or memory. In our ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 83 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…From middle childhood through adolescence, at the whole brain level, networks become more modular and segregated with age, supporting improved cognition (Satterthwaite et al, 2013b;Gu et al, 2015;Grayson and Fair, 2017;Marek et al, 2019). At the system resolution, age is associated with increases in within-system connectivity, and decreases in between-system connectivity, particularly between the default mode system and executive control and attention systems (Fair et al, 2008;Chai et al, 2013;Satterthwaite et al, 2013b;Gu et al, 2015;Lopez et al, 2019;Jones et al, 2021). At the regional level, effects are less consistent, perhaps because findings vary widely depending on the age range studied (Grayson and Fair, 2017;Morgan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From middle childhood through adolescence, at the whole brain level, networks become more modular and segregated with age, supporting improved cognition (Satterthwaite et al, 2013b;Gu et al, 2015;Grayson and Fair, 2017;Marek et al, 2019). At the system resolution, age is associated with increases in within-system connectivity, and decreases in between-system connectivity, particularly between the default mode system and executive control and attention systems (Fair et al, 2008;Chai et al, 2013;Satterthwaite et al, 2013b;Gu et al, 2015;Lopez et al, 2019;Jones et al, 2021). At the regional level, effects are less consistent, perhaps because findings vary widely depending on the age range studied (Grayson and Fair, 2017;Morgan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By age 12 years, however, the organization of the sensory-association gradient resembles that of adults; development of the primary sensory-association gradient may be mediated by changes in network architecture (Dong et al, 2021;Xia et al, 2022). Functional network architecture has been shown to have cognitive consequences: youth with more segregated networks, and in particular taskpositive (i.e., attention and control systems) and task-negative (i.e., default mode) systems, perform better on a wide variety of cognitive tasks (Gu et al, 2015;Lopez et al, 2019;Marek et al, 2019;Jones et al, 2021;Xia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The elevated connectivity in hyperactive/impulsive individuals would therefore be similar to younger individuals without these difficulties. Indeed, previous evidence in this at-risk cohort demonstrated that the CEN and a limbic network, which overlaps with the SN component in the mOFC, did not segregate with age relative to comparison children (34). Exploratory analyses in the current study also suggested that the effects of age on CEN-DMN functional connectivity differed between the at-risk and comparison samples.…”
Section: Discussionmentioning
confidence: 71%
“…In the current study, we used a large transdiagnostic sample of children who experience difficulties in cognition and behavior, with variable scope and impact (27)(28)(29)(30)(31)(32)(33)(34). Children were referred to the sample by professionals in children's educational or clinical services, and are at elevated risk of educational underachievement (35), underemployment (36), and mental health difficulties (37).…”
mentioning
confidence: 99%
“…Based on prior work, we identified which of the delineated networks are those most likely to exhibit developmental segregation. Previously, we have detailed that the functional networks undergoing the most dramatic developmental segregation are those lying at the top of the cortical hierarchy 6 , and other publications have similarly suggested that default-mode networks undergo developmental segregation 43,44 . Accordingly, we evaluated each network for its hierarchical position and overlap with canonical functional networks, and selected the single network fulfilling both a priori criteria (high in hierarchy and overlapping with the canonical default mode).…”
Section: Sensitivity and Specificity Analysesmentioning
confidence: 81%